AN ANALYSIS OF METHODS AND PROCEDURES IN TRANSLATING FRIENDSTER WEB PAGES - Ramila Herdianti, - (2009)
This paper is entitled An Analysis of Methods and Procedures in Translating Friendster Web Pages. This study is aimed to identify the translation methods and procedures mostly found in Friendster. This study employs a descriptive qualitative method to gain the data of sentences and phrases in Friendster web pages. The data were categorized based on their types and analyzed based on Newmark's translation theory. The research findings showed that there were five translation methods found; faithful (69.38%), communicative (17.92%), literal (6.19%), word-for-word (5.21%), and free translation method (1.30%). The most frequently used method in translating sentences is faithful. It indicated that the translation paid more attention to precise contextual meaning of the source language. Furthermore, there were eight translation procedures found; couplets including 2 triplets (34.4%), through-translation (23.2%), transposition (18.4%), naturalization (11.2%), transference (7.2%), synonymy (2.4%), modulation (2.4%) and expansion (0.8%). The use of couplets in translating phrases showed that the words were difficult to translate only with a single procedure. Thus, the translation was done by combining one procedure with other procedures.